Cleaning Transferred Graphene for Optimization of Device Performance. Issue 11 (30th April 2019) - Xiao, Zhuocong; Wan, Qifang; Durkan, Colm
Abstract: Much has been made of the potential electrical properties of graphene, but still in many cases, unintentional doping leads to these not being fully realized. In the processing of graphene, the step which leads to most of this doping is the transfer from the growth substrate leaving unwanted chemical residue on the graphene surface. A comparison of the techniques most commonly used to remove this residue is presented showing that most effective cleaning can be obtained using ionic solutions rather than the more commonly used organic solvents. The physical and electrical properties of graphene treated using these solutions are assessed by a combination of atomic force microscopy, Raman spectroscopy, Kelvin‐Probe force microscopy, and contact resistance/charge neutrality point measurements, and it is shown how to remove residue effectively and reduce contact resistance without adversely affecting the graphene. Abstract : Ionic solutions remove transfer residues on graphene better than organic solvents. After growth, graphene is transferred onto insulating substrates for electrical measurements. Here, it is shown how to remove PMMA residues using NaCl and HCl solutions, as conventional solvents are ineffective at removing them. This is used to improve contact resistance while minimizing unintentional doping of the graphene.